Preparation and evaluation of a metallic foam catalyst for steam-CO2 reforming of methane in GTL-FPSO process - Park, Daeil; Moon, Dong Ju; Kim, Taegyu (ELSEVIER SCIENCE BV, 2014)
A metallic foam catalyst was used to improve the heat transfer of a reactor for the steam-CO2 reforming (SCR) of methane in the GTL-FPSO (gas to liquid-floating production storage and offloading) process. The metallic foam catalyst was prepared and examined by scanning electron microscopy, fall-off test and SCR reaction. The radial heat transfer was characterized in terms of the Nusselt number and was compared with the pellet catalyst to confirm the improvement in the heat transfer of the metallic foam catalyst. As a result of the fall-off test, the adhesion strength was highest at an Al2O3/AIP molar ratio of 5. The Nusselt number of the metallic foam catalyst was higher than that of the conventional pellet catalyst. Therefore, the reformer had a uniform temperature distribution along the catalyst-bed when the metallic foam catalyst was used. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: SYNTHESIS GAS; SUPPORTS; DEPOSITION; HYDROGEN; SYNGAS; MASS; CO